1999
DOI: 10.1089/104454999315051
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Manganese Superoxide Dismutase in Transformed Cells Is Associated with Increased Cytosine Methylation of the SOD2 Gene

Abstract: Tumor cells express lower levels of manganese superoxide dismutase (MnSOD) than their normal counterparts. Enforced expression of MnSOD reverses the malignant phenotype of many transformed cells, suggesting that SOD2 is a tumor suppressor. The SOD2 gene contains a large CpG island spanning > 3.5 kb that starts near the 5' edge of the promoter and extends into intron 2. We hypothesized that the difference in SOD2 expression between tumor cells and their normal cell counterparts might be secondary to differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 46 publications
0
52
1
1
Order By: Relevance
“…[21][22][23] The expansive CpG island at the 5' end of the SOD2 gene makes it a candidate for control by DNA methylation. 10 Therefore, we tested the hypothesis that decreased MnSOD expression in human breast cancer cells was associated with increased SOD2 promoter cytosine methylation. To test this hypothesis we used bisulfite sequencing to analyze eight CpG sites located between -1422 and -1164 upstream from the transcription initiation start site of MnSOD (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[21][22][23] The expansive CpG island at the 5' end of the SOD2 gene makes it a candidate for control by DNA methylation. 10 Therefore, we tested the hypothesis that decreased MnSOD expression in human breast cancer cells was associated with increased SOD2 promoter cytosine methylation. To test this hypothesis we used bisulfite sequencing to analyze eight CpG sites located between -1422 and -1164 upstream from the transcription initiation start site of MnSOD (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, hypermethylation within the second intron of SOD2 was associated with decreased MnSOD levels in immortalized fibroblasts. 10 More recently, additional studies have shown that methylation of the SOD2 promoter decreases the expression of MnSOD in multiple myeloma. 26 Epigenetic silencing by DNA methylation is heritable, but is dependent upon the activity of DNA methyltransferases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations